History of dentistry in ancient Egypt - Nadia Lotfy (Academy Publishing Center, 2022)
Egyptian civilization is the oldest one allover the world. Dentistry was practiced among ancient Egyptians and it is documented by many ways such as The study of ancient remains, ancient teeth, Mummification and the translation of ancient papyri. This work reviews the dental diseases that ancient Egyptians suffered from such as Tooth wear, Dental abscesses, Disease of the gum and Dental caries.      The ancient Egyptians managed their dental problems by many ways such as utilization of             drugs made of herbs and making the oldest toothpaste in the world. They managed carious teeth by filling materials, Dental restorations and even tried to make implants. Surgical treatment by dental instruments was also recorded.